RANCANGAN BUKU SAKU KEANEKARAGAMAN JAMUR BASIDIOMYCOTA PADA MATERI FUNGI KELAS X SMA - Ardiani, Dilla; Zulfarina, Zulfarina; Sayuti, Irda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to design a Pocket Book of Basidiomycota Mushrooms for Class X Biology learning with Fungi as a learning resource in the form of a pocket book. This research was carried out at the Faculty of Teacher Training and Education, Riau University in September – November 2021. The basics in the stages of designing this pocket book are the Curriculum analysis stage and the pocket book design stage. The curriculum analysis stage is carried out by reviewing the 2013 curriculum and analyzing learning materials. The pocket book design stage is carried out by designing the syllabus and lesson plans first then the pocket book design is carried out, where the pocket book design consists of a cover, preface, table of contents, curriculum level, introduction, contents, and bibliography. The type of research used is descriptive qualitative where the method used is a survey method. Based on the results of the potential analysis, there are 29 types of Basidiomycota Mushrooms in the Arboretum Area, Riau University which can be used as a pocket book design on Fungi material in Biology learning class X SMA.Key Words: Pocket Book, Learning Media, Basidiomycota